Assessment of the geological heritage of Cape Mondego Natural Monument (Central Portugal) - Rocha, João Nuno Correia (2014)
In the western coast of Portugal, Cape Mondego is a well-known set of outcrops due to its international stratigraphic relevance given by the establishment of two stratotypes: the Global Boundary Stratotype Section and Point (GSSP) for the base of the Bajocian Stage and the Auxiliary Stratotype Section and Point (ASSP) for the base of the Bathonian Stage. The remarkable geodiversity of these Jurassic outcrops justifies the implementation of strategies in order to conserve and promote the geosites, which include a rich palaeontological record of macrofossils, microfossils and dinosaur footprints. Based on the exceptional quality of the geological record, on its international importance and on its high scientific and educational values, this area was classified in 2007 as Natural Monument. However, no geosite systematic inventory was ever done. In this work, a systematic identification, characterization and assessment of geosites was done in the Natural Monument. Based on fieldwork and published data, a first set of 32 potential geosites was identified taking into account their scientific, educational and touristic values. After the application of three criteria (representativeness, singularity and proximity) this group of 32 potential geosites was reduced to 12. These 12 geosites were assessed resulting on the establishment of a medium to high ranks for both educational and geotouristic potential uses. Based on this assessment, some valuing strategies were proposed, aiming at the sustainable use and the promotion of the Natural Monument geosites, within the scope of both educational and geotouristic activities addressed to secondary school students and the general public.